词汇搜索游戏法对X小学四年级学生汉语阅读能力的有效性: The Effectiveness of the Vocabulary Search Game Method on Mandarin Vocabulary Reading Competence in Grade 4 Students of SD X Surabaya - Dionisius Ardian; Maria Apriana; Ong Peter Leonardo; Yibo Fu (International Journal of Chinese Interdisciplinary Studies, 2025)
小学学校教授普通话，它是继英语之后的第二大国际语言。学生在学习普通话的过程中面临着许多挑战，其中之一是阅读能力。然而，如果教师选择并实施适当的方法，学生的学习动力和热情将会更加提高。本研究将探讨词汇搜索游戏法在提升泗水X小学四年级学生词汇阅读能力方面的有效性。本研究采用实验法，并进行前测和后测，采用定量方法和游戏法。结果表明，游戏法学习汉语词汇更为有效，因为它可以提高泗水X小学四年级学生的学习成果。这种游戏教学法比课堂讲授更有效，因为学生常常对学习过程觉得无聊，从而失去兴趣。游戏教学法可以改变学习方式，帮助学生理解并培养学习兴趣。此外，游戏并非个人活动，而是一项多人参与的小组活动。小组游戏具有诸多益处，有助于与他人建立积极的关系。小组游戏的许多积极方面也有助于学生的成长和发展。我们也可以看出，学生通过这种游戏式学习方式的学习效果有所提升。预前测结果也证明了这一点，当时只有两名学生达到了最低完成标准，占全班学生的7.14%。然而，在使用游戏发之后，通过的学生人数增加到22人，占全班学生的78.58%，增加了71.44%.现有数据表明，采用这种游戏方式非常有效，提高了学生学习普通话的兴趣。 Mandarin is taught in primary schools and it is the second most popular international language after English. Students face many challenges in learning Mandarin, one of which is reading ability. However, if teachers choose and implement appropriate methods, students' motivation and enthusiasm will be improved. This study will explore the effectiveness of the vocabulary search game method in improving the vocabulary reading ability of fourth-grade students in X Primary School, Surabaya. This study adopts an experimental method and conducts pre-tests and post-tests, using quantitative methods and game methods. The results show that the game method is more effective in learning Chinese vocabulary because it can improve the learning outcomes of fourth-grade students in X Primary School, Surabaya. We can also see that students have improved their learning outcomes through this game-based learning method. This was also confirmed by the pre-test results, when only two students reached the minimum completion standard, accounting for 7.14% of the class. However, after using the game, the number of students who passed increased to 22, accounting for 78.58% of the class, an increase of 71.44%. The existing data shows that this game-based approach is very effective and has increased students' interest in learning Mandarin.